Histone Modification Pathways Suppressing Cryptic Transcription - Hong-Yeoul Ryu (Epigenomes)
Cryptic transcription refers to the unintended expression of non-canonical sites within the genome, producing aberrant RNA and proteins that may disrupt cellular functions. In this opinion piece, I will explore the role of histone modifications in modulating cryptic transcription and its implications for gene expression and cellular integrity, particularly with a focus on H3K36 and H3K4 methylation marks. H3K36 tri-methylation plays a crucial role in maintaining chromatin integrity by facilitating the recruitment of the Rpd3S histone deacetylase (HDAC) complex, which helps restore closed chromatin states following transcription and prevents cryptic initiation within gene bodies. In parallel, crosstalk between H3K4 di-methylation and histone ubiquitylation and sumoylation is critical for recruiting the Set3 HDAC complex, which maintains low histone acetylation levels in gene bodies and further suppresses cryptic transcription. Therefore, by elucidating these regulatory mechanisms, this opinion highlights the intricate interplay of histone modifications in preserving transcriptional fidelity and suggests potential pathways for future research to develop novel therapies for age-related disorders and other diseases associated with dysregulated gene expression.